Idosos em situaç\~ao de isolamento social: Uma abordagem macrossetorial - Luciana Jaccoud (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This article analyzes the situation of social isolation among the elderly, considering both its impacts on health and well-being and the interventions that have been mobilized to combat it. Based on international literature on the topic, the first part of the text discusses the negative influences of social isolation (and loneliness) on the health and well-being of the elderly. It also presents an overview of the interventions and services that have been mobilized to address the issue. The Brazilian case is treated in the second part of the text based on data from the 2019 National Health Survey, which allows us to draw an approximate picture of the dynamics of social interaction and social isolation of the elderly. Also in Brazil, social isolation has been the subject of actions in the fields of health and social assistance, but its integration between those policies is still incipient. Finally, it is suggested that the mobilization of the macrosectoral approach to social security may favor reflection on this public and their vulnerabilities, as well as contribute to the implementation of articulation instruments in favor of greater coordination between policies and their interventions.
Keywords: I31; I38; 330; elderly; social isolation; health; social assistance; social security; macrosectoral; intersectoral